From the Environment to the Connatural World: Human Being in Search of his oίκος - Łepko, Zbigniew; Sadowski, Ryszard F. (Studia Ecologiae et Bioethicae, 2017)
This article refers to the proposed by K. M. Meyer-Abicha allegory of a man wandering in search of his oίκος. This migration is a picture of the history of mankind, which is synonymous with the cultural history of nature, that is, the presence of humans in nature through his culture. In that sense, the cultural history of nature can be divided into three main stages, characterized by both the way of understanding and treatment of nature by man. Each stage of this history is marked by a smooth change of styles of human presence in nature. The wide spectrum of the styles extends to the field designated by understanding oίκος as Umwelt (environment) and Mitwelt (connatural world).